Analisis Safety Patrol Berbasis IPBR dan HIRARC Untuk Mengurangi Kecelakaan Kerja di Terminal Jamrud - Satriya, Rafdi Ma’ruf; Kartikawati, Marina; Kalmah, Kalmah; Hidayati, Ratna (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2025)
PT Pelindo Multi Terminal is a company engaged in loading and unloading services for liquid bulk, dry bulk and containers. Hazard Identification, Risk Assessment and Risk Control (HIRARC) is a method for identifying potential hazards that exist in each type of work. The aim of this research is to determine hazard identification, risk assessment and risk control using the Hazard Identification, Risk Assessment and Risk Control (HIRARC) method at PT Pelindo Multi Terminal. Research was carried out on all aspects of each liquid bulk to dry bulk operation which have the potential to cause accidents and occupational health. Data collection techniques are field observation, interviews and documentation. Descriptive data analysis using the HIRARC model with comparison of the effectiveness of IBPR. The results of the research show that IPBR risk control in the low risk category shows an increase in the presentation of signs of success in risk control, in this case there is an increase in the low risk category by 55%, while HIRARC risk control in the low risk category shows an increase in the presentation of signs of success in risk control. , in this case there is an increase in the low risk category by 90%, in this case it can be seen that HIRARC is more effective in controlling work risks. PPE equipment is adjusted to the type of work being carried out because there are still inconsistencies in wearing PPE. Keywords: Hazard Identification, Risk Assessment, Risk Control, HIRARC.